Token Economy: Strategi Efektif Tingkatkan Tooth Brushing Initiative pada Anak Usia Dini - Lidya Yuliani; Mutiara Rahma Eldita; Elvita Putri; Lisa Arista; Aliyan Syarif Mukhtar; Bulan Permata Sari; Rahma Rezki Elvika (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Responsibility is a key factor underlying children's attitudes, influencing their problem-solving abilities and self-confidence. This study explores the effectiveness of economic tokens in enhancing responsibility among preschool-aged children, particularly regarding the initiative to brush their teeth. Utilizing a single-case experimental design with one 4-year-old subject, data were collected through interviews, observations, and documentation, and analyzed descriptively. Results indicated a decline in responsible behavior from baseline 1 (A1) to baseline 2 (A2). However, from treatment 1 (B1) to treatment 2 (B2), there was an increase in responsible behavior. In conclusion, the economic token technique proved effective in improving the initiative to brush teeth in children.